Instability analysis of reinforced concrete walls with various support conditions. (9th February 2017) - Ho, Nhat‐Minh; Doh, Jeung‐Hwan; Fragomeni, Sam
Summary: Axially loaded reinforced concrete walls can be designed using simplified design methods given in codes such as the Australian Concrete Standard Code (AS3600‐09) and the American Concrete Institute Code (ACI318‐14). However, these practical equations are based on empirical models, and their scope of application is still limited. In particular, walls with the various support conditions, high slenderness, and aspect ratios have been given little treatment. Recent research has been undertaken on the applicability of more reliable and accurate wall design methods. This paper initially presents a derived numerical technique incorporated in a computer program (WASTABT), to implement the iterative analysis for concrete walls with various support conditions. The outputs from the WASTABT program are verified using the results obtained from previous experimental results. A parametric study is then conducted using the verified computer‐based numerical technique to analyse axially loaded reinforced concrete panels. The study focuses on the effect of varying panel properties such as slenderness ratios, aspect ratios, concrete strengths, eccentricities, and reinforcement ratios, along with varying support conditions.